Overview on marine oil spills and impacts on the marine biodiversity - Thanh, Dang Ngoc (Academia Journal of Biology, 2012)
In the paper, the author presents an overview on the marine oil spills and its impacts on the marine environmental conditions, biodiversity and the living resources. Some information on greatest oil spills in the world and in the South East Asian Sea area during the period 70’s years up to present times is given. Impacts of oil spills are always a catastrophic event for marine environment and living organisms. Factors which determine oil spills impacts include: oil type, local geographical position, climate and season, oceanographic conditions and biological characteristics of the area. The range of biological impacts encompass: physical and chemical alteration of natural conditions of the marine environment and particularly natural habitats, physical effects on flora and fauna, ecological changes in ecosystems. Effects on living organisms and habitats of oil pollutants caused by oil spills may be acute effects (short-term effects) or long-term effects, each has its own consequences. Impacts of oil spills are revealed at different life level: species, populations, communities and ecosystems.... For this reason, to evaluate the impacts of oil spills, it needs a comprehensive view to reveal the total effects of the catastrophe on the biodiversity and the living resources of the polluted marine area.